2019
DOI: 10.1111/imj.14150
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulator use does not prevent first loss of response to anti‐tumour necrosis factor alpha therapy in inflammatory bowel disease: long‐term outcomes in a real‐world cohort

Abstract: Background Recent prospective studies suggest combination therapy with immunomodulators improves efficacy, but long‐term data is limited. Aim To assess whether anti‐tumour necrosis factor alpha (anti‐TNF) monotherapy was associated with earlier loss of response (LOR) than combination therapy in a real‐world cohort with long‐term follow up. Methods A retrospective audit was conducted of inflammatory bowel disease patients receiving anti‐TNF therapy in a tertiary centre and specialist private practices. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The median time to LOR was not different between groups. The data suggest that patients treated with anti-TNF monotherapy have similar LOR rates as patients on anti-TNF combination therapy (95). Switching to another anti-TNF may aid 50% of patients with IBD.…”
Section: Current Methods For Overcoming Ineffectiveness Of Anti-tnfs mentioning
confidence: 99%
“…The median time to LOR was not different between groups. The data suggest that patients treated with anti-TNF monotherapy have similar LOR rates as patients on anti-TNF combination therapy (95). Switching to another anti-TNF may aid 50% of patients with IBD.…”
Section: Current Methods For Overcoming Ineffectiveness Of Anti-tnfs mentioning
confidence: 99%
“…About 50% of subjects with Crohn’s disease or ulcerative colitis develop LOR to infliximab following an early response to the drug [ 82 ]. There is no difference in time to LOR between subjects treated using regimens comprising several drugs or different anti-TNF agents [ 83 ]. Switching between anti-TNF agents, dose intensification, and adding an immunomodulator to suppress immunogenicity may overcome LOR with moderate success [ 84 , 85 ].…”
Section: Drug Resistance In Common Chronic Diseasesmentioning
confidence: 99%
“…In a study by Billiet et al [7], concomitant with an IMM was not favorable with regards to long-term outcomes for patients with CD. In addition, a recent long-term retrospective cohort study revealed that there is no difference in the development of LOR to anti-TNF agents between monotherapy and combination IMM therapy [8].…”
mentioning
confidence: 99%